2018
DOI: 10.1186/s13287-018-0903-4
|View full text |Cite
|
Sign up to set email alerts
|

Early gestational mesenchymal stem cell secretome attenuates experimental bronchopulmonary dysplasia in part via exosome-associated factor TSG-6

Abstract: BackgroundMesenchymal stem cells (MSCs) are promising tools for the treatment of human lung disease and other pathologies relevant to newborn medicine. Recent studies have established MSC exosomes (EXO), as one of the main therapeutic vectors of MSCs in mouse models of multifactorial chronic lung disease of preterm infants, bronchopulmonary dysplasia (BPD). However, the mechanisms underlying MSC-EXO therapeutic action are not completely understood. Using a neonatal mouse model of human BPD, we evaluated the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 83 publications
4
118
0
2
Order By: Relevance
“…The identification of astroglial activation in pigs supports the capacity of AD-MSCs to reduce GFAP expression predominantly in the caudal direction from the epicenter of injury, similar to what we found in rats although to a lesser degree. The potential reduction in astroglial activation was attributed to the ability of MSCs to decrease cyclooxygenase-2 and IL-6 cytokine levels [18,59] and secretion of TNF-stimulated gene-6 [69][70][71][72], which consequently decreases NF-κB signaling, resulting in modulation of A1 neuroinflammatory reactive astrocytes [73,74]. We found no effect of AD-MSCs treatment on microglial activation in pigs, similar to results in rats.…”
Section: Discussionsupporting
confidence: 74%
“…The identification of astroglial activation in pigs supports the capacity of AD-MSCs to reduce GFAP expression predominantly in the caudal direction from the epicenter of injury, similar to what we found in rats although to a lesser degree. The potential reduction in astroglial activation was attributed to the ability of MSCs to decrease cyclooxygenase-2 and IL-6 cytokine levels [18,59] and secretion of TNF-stimulated gene-6 [69][70][71][72], which consequently decreases NF-κB signaling, resulting in modulation of A1 neuroinflammatory reactive astrocytes [73,74]. We found no effect of AD-MSCs treatment on microglial activation in pigs, similar to results in rats.…”
Section: Discussionsupporting
confidence: 74%
“…Willis et al [73] showed that MSC-derived exosomes modulated the lung macrophage phenotype by suppressing the pro-inflammatory 'M1' state and enhancing an anti-inflammatory 'M2-like' state both in vitro and in vivo. Interestingly, another study demonstrated the repair effect of MSC-derived exosomes in a BPD animal model [74]. MSC-derived exosomes can repair the lung injury and improve BPD-associated brain injury as revealed by decreased brain cell death and reversed hypomyelination.…”
Section: Msc-derived Secretomes For Bpd Therapymentioning
confidence: 99%
“…Yan et al demonstrated that human umbilical cord MSC (hUC-MSC) exosomes promoted hepatocyte recovery from oxidative stress via the antioxidant and antiapoptotic effects of exosomal glutathione peroxidase1 (GPX1) both in vitro and in vivo, however, GPX1 knockdown was found to delay this hepatoprotective effect [72]. MSC exosomes have also been reported to mediate several known functions of MSCs in premature infant diseases, including modulating inflammatory/immune responses and reducing fibrosis, apoptosis, and oxidative stress [73][74][75][76]. However, more in-depth research is required to explore the mechanisms underlying the effects of exosomes.…”
Section: Msc-derived Evs: a Therapeutic Vector Of Mscs?mentioning
confidence: 99%
See 2 more Smart Citations